Estrogen‐Related Receptor Gamma Gene Therapy Promotes Therapeutic Angiogenesis and Muscle Recovery in Preclinical Model of PAD - Danesh H. Sopariwala; Andrea S. Rios; Addison Saley; Ashok Kumar; Vihang A. Narkar (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2023)
Background Peripheral arterial disease and critical limb ischemia are cardiovascular complications associated with vascular insufficiency, oxidative metabolic dysfunction, and myopathy in the limbs. Estrogen‐related receptor gamma (ERRγ) has emerged as a dual regulator of paracrine angiogenesis and oxidative metabolism through transgenic mouse studies. Here our objective was to investigate whether postischemic intramuscular targeting of ERRγ via gene therapy promotes ischemic recovery in a preclinical model of peripheral arterial disease/critical limb ischemia. Methods and Results Adeno‐associated virus 9 (AAV9) Esrrg gene delivery vector was developed and first tested via intramuscular injection in murine skeletal muscle. AAV9‐Esrrg robustly increased ERRγ protein expression, induced angiogenic and oxidative genes, and boosted capillary density and succinate dehydrogenase oxidative metabolic activity in skeletal muscles of C57Bl/6J mice. Next, hindlimb ischemia was induced via unilateral femoral vessel ligation in mice, followed by intramuscular AAV9‐Esrrg (or AAV9‐green fluorescent protein) gene delivery 24 hours after injury. ERRγ overexpression increased ischemic neoangiogenesis and markers of endothelial activation, and significantly improved ischemic revascularization measured using laser Doppler flowmetry. Moreover, ERRγ overexpression restored succinate dehydrogenase oxidative metabolic capacity in ischemic muscle, which correlated with increased mitochondrial respiratory complex protein expression. Most importantly, myofiber size to number quantification revealed that AAV9‐Esrrg restores myofibrillar size and mitigates ischemia‐induced myopathy. Conclusions These results demonstrate that intramuscular AAV9‐Esrrg delivery rescues ischemic pathology after hindlimb ischemia, underscoring that Esrrg gene therapy or pharmacological activation could be a promising strategy for the management of peripheral arterial disease/critical limb ischemia.